إدارة التنظيمية اللغة العربية بمعهد دار الأخوة للبنات 2 مالانج - Kotta, Kamila Maryam; Hanifa, Faricha Nidaul; Rahmatunnur, Sari; Rahmatunnur, Sari Rahmatunnur (Al-Muyassar: Journal of Arabic Education, 2024)
AbstractThis study discusses about: 1) the management of the mandatory Arabic language environmental program at Darul Ukhuwwah Putri Islamic Boarding School 2, 2) The division of tasks in the management of mandatory Arabic language environmental program at Darul Ukhuwwah Putri 2 Islamic Boarding School  Malang. In this study, researchers used a qualitative descriptive approach. The data collection techniques were carried out by using documentation, observation and interview techniques. After the data is collected, data analysis is carried out by condensing data, presenting data, and having a conclusions/verification. The results of this study, it can be concluded that the management of mandatory Arabic language environmental program at Pondok Pesantren Darul Ukhuwwah putri 2 Malang which is supported by active activities such as the distribution of vocabulary, conversation, speech practice, language festivals, and evaluation of Arabic language programs. The management of the mandatory Arabic language environmental program organization uses a coordination system. This can be proven by looking at the duties of the manager under the auspices of the general chairman, after coordinating with the person in charge of the section, and in each program that is in the Arabic language section because Arabic programs and organizations in general have a line and staff structure model. Management of program organization at Darul Ukhuwwah Putri 2 Islamic Boarding School is well structured, and this is evidenced by the division of  tasks starting from the caregiver, general chairpersons, language departments, and each department coordinator. The division of tasks for administrators and teachers recruits students and teachers who serve in the foundation. The administrators in the Arabic language program have responsibility and authority in the organizational system in the Arabic language mandatory environmental program.Keywords: Arabic Language, Management, Organizing. مستخلص البحثهذه الدراسة تناقش عن : 1) إدارة التنظيم البرنامج البيئة اللغةالعربية بمعهد دار الأخواة للبنات 2 مالانج، 2) تقسيم الوظائف في إدارة التنظيم البرنامج البيئة اللغة العربية بمعهد دار الأخواة للبنات 2 مالانج.  استخدمت الباحثات المنهج  الوصفي النوعي في هذه الدراسة. كانت تقنيات جمع البيانات في هذه الدراسة من التوثيق والملاحظات و المقابلات.  بعد جمع البيانات يتم إجراء تحليل البيانات  بتقليل البيانات، عرض البيانات، رسم الاستنتاجات والتحققها. وأما اانتائج لهذه الدراسة أن إدارة التنظيم البرنامج البيئة الغة العربة بمعهد دار الأخواة للبنات 2 مالانج  هو مدعومة من الأنشطة النشطة كتوزع المفردات، والمحادثات، والمحاضرة، والمهرجانات اللغوية، وتقييم البرنامج اللغة العربية، وغيره. تستخدم إدارة التنظيم البرنامج البيئة اللغة العربية نظام التنسيق ودليل عنه يعنى من النظر  واجبات المدير تحت رعاية الرئيس العام بعد التنسيق مع المسؤول عن القسم،  في كل برنامج موجود في قسم اللغة العربية لأن البرناج و المنظمات اللغة العربية بشكل عام لديها نموذج هيكل الخط والموظفين. أن إدارة التنظيم البرنامج  بمعهد دار الأخواة  للبنات 2 مالانج  منظمة بشكل جيد ودليل عنه يتضح من خلال تقسيم الوظائف  بداء من المشرف والرئيس العام وقسم اللغة والمنسق كل القسم. تقسيم الوظائف المدبر والمعلم يشغل من الطلاب والمعلم الذي يعمل في المؤسسة. المدبرات في هذا البرنامج خاصة اللغة العربية يجدون مسؤليات وصلاحيات في النظام التنظيم البرنامج البيئة اللغة العربية.الكلمات المفتاحية: اللغة العربية، الإدارة، التنظيم